The Divine Will on Riba - Tahir, Sayyid (Islamic Economics Institute, King Abdul Aziz University Jeddah, 2014)
The "Divine Will on Ribā" means what Allah SWT desires the believers to do through His dislike, condemnation and prohibition of ribā in the Qurãn. This study investigates this matter. It represents a departure from the dominant tradition that focuses on what ribā is. Methodology of analysis is explained at the outset. Data from the Qurãn are reproduced. A preliminary conclusion is first drawn as to what the Basic Edict on ribā in the Qurãn is. That is then refined by closely examining the communication style in the Qurãn and bringing into the picture the Sunnah of the Prophet SAAWS traceable to selected Aḥadīth on ribā. Final conclusion on the 'Divine Will on Ribā' is this: all loans, debts and similar other exchanges must be settled on an equal basis (in terms of units of the object of exchange), and there should not be even an indirect violation of this principle. The study also explains the ḥikmah (Divine Wisdom) and practical implications of the Divine Will.